High post-flowering phosphorus status promotes the tolerance of soybean to terminal heat stress - Laira, Matheus D.; Andrade, Sara A.L.; Silveira, Neidiquele M. [UNESP]; Machado, Eduardo C.; Ribeiro, Rafael V.; Zambrosi, Fernando C.B. (Elsevier, 2023)
Global air temperature is rising and resulting in higher frequency and intensity of extreme climatic events. This scenario threatens food security, requiring measures to mitigate the harmful effects of heat stress on agricultural production. Therefore, our study focused on understanding how phosphorus (P) availability during the reproductive period affects seed weight responses of soybean to terminal heat stress. The experiment was carried out in a complete 3 × 2 factorial design, with varying post-flowering P supply (severe deficiency: 20 μmol P L−1; mild deficiency: 100 μmol P L−1; sufficiency: 500 μmol P L−1) and thermal regimes imposed during the seed filling phase (control: 28.0/18.0 °C; heat stress: 42.0/28.5 °C). Our results revealed that seed weight and yield were unaffected by heat stress in the plants grown under P sufficiency, whereas a detrimental effect of warming on these traits was found in the plants facing post-flowering P deficiency. Sufficient post-flowering P supply alleviated also the harmful effects of heat stress on the integrity of the photosynthetic apparatus, which contributed to improve biomass partitioning to the harvestable organs by extending seed filling duration. Moreover, heat stress disturbed sink metabolism and caused reduction in the concentration of oil and starch solely in the seeds of the plants exposed to P limitation. In conclusion, maintaining adequate post-flowering P supply proves critical in enhancing soybean's tolerance to terminal heat stress by supporting essential processes involved in effective seed filling. Consequently, implementing precise P nutritional management during the reproductive period of soybean might be a promising approach to improve crop yield stability in challenging environmental conditions.
Keywords: Biomass partitioning; Global warming; Glycine max; Nutritional stress; Seed filling